Pharmacokinetic and pharmacodynamic properties of enrofloxacin in Southern crested caracaras (Caracara plancus) - Waxman Dova, Samanta (2013)
To determine the dosage of enrofloxacin in southern crested caracaras (Caracara plancus), plasma concentrations of enrofloxacin were measured by high-performance liquid chromatography after intravenous (IV) (5 mg/kg) and intramuscular (IM) (10 mg/kg) administration. This compound presented a relatively high volume of distribution (2.09 L/kg), a total body clearance of 0.24 L/kg·h, and a long permanence as shown by an elimination half-life of 7.81 hours after IV administration and a terminal half-life of 6.58 hours after IM administration. The areas under the concentration-time curves (AUC) were 21.92 and 34.38 μg·h/mL for IM and IV administration, respectively. Enrofloxacin was rapidly absorbed after IM administration with a time to reach maximum concentration of 0.72 hours and bioavailability of 78.76%. After IM administration, the peak drug concentration (Cmax) was 3.92 μg/mL. Values of minimum inhibitory concentration (MIC), Cmax, and AUC have been used to predict the clinical efficacy of a drug in treating bacterial infections, with a Cmax/MIC value of 10 and an AUC/MIC ratio of 125-250 associated with optimal bactericidal effects. By using the study data and a MIC breakpoint of 0.25 μg/mL, values of Cmax/MIC were 13.74 and 15.94 and for AUC/MIC were 90.73 and 139.63, for the IV and IM routes respectively. For the treatment of infectious diseases caused by microorganisms with MIC ≤0.25 μg/mL, the calculated optimal dosages were 7.5 and 9.5 mg/kg q24h by the IV and IM routes, respectively. For less susceptible bacteria, a dose increase should be evaluated. To treat caracara by the IV route against microorganisms with MIC ≤0.25 μg/mL, the dose should be higher than the 5 mg/kg used in our study, but possible side effects derived from an increase in the IV dose and efficacy in sick birds should be assessed.